Estudo da alfabetização científica de alunos do 9° ano do Ensino Fundamental de um colégio particular de São Paulo-SP: elaboração de uma proposta de formação para os professores de Ciências - Coppi, Marcelo Alves (2016)
Science education has the main objective to use the knowledge of scientific and technological nature to do the student becomes a citizen able to understand and interfere in the world who lives. To enable this development during the basic education, some specific sciences skills are required, as the construction of the scientific reasoning through observation, experimentation, survey, development, test, refutation and abandonment of hypotheses, relations establishment between facts, phenomena or ideas. To measure the students are appropriating these skills, they pass to be capable to employ and use Science in everyday troubleshooting, being considered "scientifically literate". So, Scientific Literacy are defined as the set of Scientific and Technological knowledge that empowers the individual to understand, interpret and act in the world he lives, acting, so how as a citizen. Understanding that fit to Science teachers and the School create a bridge between scientific and technology concepts with everyday problems and phenomena an end to develop of the student, it was sought in this work to analyze the Scientific Literacy of students of the 9th grade of Elementary School, by using the Test of Basic Scientific Literacy – TBSL, developed by Laugksch and Spargo, as so, the analyze the Plans Base of Science Education based on the matrix proposed by the Science for All Americans program. The results point that only 15,3% of students are considered scientifically literate. From this diagnosis to the level of Science Literacy of these students, was drafted a proposal training for the Science Teachers in service which allow reformulate the School Sciences courses, indicating the basic skills that should be developed, and also, the skills that the students have greater difficulties